COMPREHENSIVE METHODS OF TEACHING ENGLISH IN TECHNICAL UNIVERSITIES - Azizova Makharam Rashitovna (Modern American Journals, 2025)
The article examines modern approaches to teaching English in technical universities, focusing on the integration of language learning with professional training. The growing importance of English proficiency for technical specialists is analyzed, particularly in fields such as aviation, engineering, and information technology. Traditional language teaching methods are compared with contemporary English for Specific Purposes (ESP) methodologies, highlighting their advantages and limitations. The paper presents a systematic approach to developing technical English programs that align with industry requirements and educational standards. Key challenges in curriculum design, faculty collaboration, and student assessment are discussed, along with practical solutions for implementation. The study emphasizes the need for continuous adaptation of teaching methods to meet the evolving demands of global technical professions.
Keywords: Technical English, ESP methodology, language teaching methods, higher technical education, professional communication.